Analisis Faktor Prediktor Kejadian Picky Eater pada Remaja - Riska Febriyanti; Indra Tri Astuti; Herry susanto (Journal of Health, Medical, and Psychological Studies, 2026)
Picky eating behavior refers to selective food consumption that may affect adolescents’ nutritional adequacy and increase the risk of long-term health problems. Adolescence is characterized by psychological and social transitions, as well as the development of body image, all of which may shape food preferences. This study aimed to examine the relationship between age, sex, body mass index (BMI), stress level, and peer influence and picky eating behavior among adolescents. A descriptive analytic design with a cross-sectional approach was employed. The sample consisted of 107 respondents selected through simple random sampling at SMP Negeri 20 Semarang. Data were collected using a structured questionnaire and analyzed using the chi-square test. The findings revealed no significant associations between age, sex, BMI, stress level, or peer influence and picky eating behavior (p > 0.05). Nevertheless, a tendency toward picky eating was more frequently observed among older adolescents, males, and those with lower BMI. These results suggest that picky eating behavior may be influenced not only by measurable biological or social factors but also by family dietary habits, food preferences, and body perception. Therefore, nutrition education and the promotion of healthy eating habits through collaboration among health professionals, schools, and families are essential to prevent adverse long-term nutritional outcomes.